Pre-Service Teachers’ Understanding and Perceptions Toward Assessment Literacy: A Systematic Review - Konadu, Benjamin Obeng (Psycho-Educational Research Reviews, 2025)
The study determined pre-service teachers’ understanding and perceptions toward assessment literacy. The study utilized a systematic review and synthesis of peer-reviewed empirical research publications from journals. Twenty-one peer-reviewed journal articles were acquired using a search utilizing the keywords: assessment literacy and pre-service teachers with teaching experience, sourced from EBSCO and Advanced Google Search. Seventeen of the twenty-one identified journal articles were then evaluated. The findings from these articles indicated that preservice teachers are deficient in understanding assessments and have perceptions toward assessments. Knowledge in assessment is very crucial for teachers in general to enhance their teaching practices in the classroom, which in turn improves upon students’ learning outcomes. In view of this, stakeholders of teacher training institutions should factor more in assessment literacy, both theory and practice into the curriculum to equip their pre-service teachers with more skills in assessment.